Faktor-faktor yang mempengaruhi keterlibatan pekerja: Kajian kes di Malaysia Building Society Berhad - Maizatul Dhuha, Abd. Razak (2013)
This study examines the influence of employee communication, employee development, and rewards and recognition on employee engagement in Malaysia Building Society Berhad (MBSB). The extent to which the findings can be generalized in non-Western countries such as Malaysia is the main motivation of the study. This study was carried out among 407 exempt staffs in MBSB. Data were gathered through questionnaires and analyzed by using Statistical Package for Social Science (SPSS). Correlation and regression analysis were used. The analysis showed significant influence of employee development on employee engagement. However employee communication, and rewards and recognition were found not significant in influencing employee engagement. Implications for future research and management practice are discussed